P.130: A Measurement‐Based Time and Frequency Domain Analysis of the LCD VCOM Noise. Issue 1 (1st July 2013) - Yeo, Dong‐Hee; Lee, Jae‐Seung; Sim, Jae‐Yoon; Park, Hong‐June
Abstract: A quantitative analysis on the LCD VCOM noise shows that the primary and secondary noise sources are the gate and data driver signals, respectively. The time‐domain waveform and the frequency spectrum are measured directly from the LCD VCOM node voltage and indirectly from the charge amp output of touch sensor.